2020
DOI: 10.1093/ejcts/ezaa100
|View full text |Cite
|
Sign up to set email alerts
|

Early results from a prospective, single-arm European trial on decellularized allografts for aortic valve replacement: the ARISE study and ARISE Registry data

Abstract: OBJECTIVES Decellularized aortic homografts (DAH) may provide an additional aortic valve replacement option for young patients due to their potential to overcome the high early failure rate of conventional allogenic and xenogenic aortic valve prostheses. METHODS A prospective, European Union-funded, single-arm, multicentre, safety study was conducted in 8 centres evaluating non-cryopreserved DAH for aortic valve replacement. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 29 publications
2
26
0
3
Order By: Relevance
“…Sarikouch et al 13 showed in a recent study important in vivo recellularization with noninflammatory cells in 11 of 364 patients implanted either with an aortic or pulmonary decellularized homograft between 2010 and 2017 in whom a reoperation with graft explanation was necessary for different reasons. The initial results of the multicentric European trial ARISE, analyzing this particular type of fresh decellularized homografts implanted in aortic position in 144 patients also demonstrated excellent early hemodynamic results 14 …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Sarikouch et al 13 showed in a recent study important in vivo recellularization with noninflammatory cells in 11 of 364 patients implanted either with an aortic or pulmonary decellularized homograft between 2010 and 2017 in whom a reoperation with graft explanation was necessary for different reasons. The initial results of the multicentric European trial ARISE, analyzing this particular type of fresh decellularized homografts implanted in aortic position in 144 patients also demonstrated excellent early hemodynamic results 14 …”
Section: Discussionmentioning
confidence: 93%
“…The initial results of the multicentric European trial ARISE, analyzing this particular type of fresh decellularized homografts implanted in aortic position in 144 patients also demonstrated excellent early hemodynamic results. 14…”
Section: Discussionmentioning
confidence: 99%
“…The group from Hannover published interesting and important results with decellularized aortic homografts together with a multicenter study assessing the impact of this valve type in young patients (average age 34 years) and in relation to bioprosthetic or mechanical valves and the Ross operation. 46 The authors found that the freedom from a combined endpoint of death, reoperation, structural degeneration, thrombosis or bleeding, and endocarditis was lowest with the decellularized homografts (►Fig. 4A).…”
Section: Classic Aortic Valve Surgerymentioning
confidence: 99%
“…61 Based on over Fig. 4 (A) Central image of a publication on the outcomes of decellularized homografts as possible alternative to biological or mechanical prostheses or the Ross procedure in patients requiring (redo) aortic valve replacement at young age (mean 34 years) 46 (reproduced with permission). (B) Comparison of the treatment effect of early surgical aortic valve replacement compared with conservative management in relation to the degree of chronic kidney disease 47 (reproduced with permission).…”
Section: Mitral and Tricuspid Valve Surgery Mitral Valvementioning
confidence: 99%
“…However, young and middle-aged patients requiring AV replacement are still confronted with a treatment dilemma: although mechanical valves bear the risk of thromboembolic and bleeding events, bioprosthetic substitutes have limited durability (2). Nevertheless, emerging technologies in alternative surgical treatment strategies in AV disease have not yet become an armamentarium with acceptable enduring long-term results (3)(4)(5)(6). This includes advancements such as new generations of bioprosthetic substitutes with anticipated improved long-term durability, innovative mechanical prosthesis design with reduced need for anti-coagulation, decellularized allografts with the theoretical potential to overcome the high early failure © Annals of Cardiothoracic Surgery.…”
Section: Introductionmentioning
confidence: 99%